Catalytic soot oxidation by platinum on sintered metal filters. Influence of the platinum quantity, particle size and location, and investigation of the platinum-soot contact - Hinot, Karelle (KIT Scientific Publishing, 2007)
The great challenge for next years concerning the emission of diesel engines is to develop diesel particle filters (DPF) with catalytic regeneration systems. This work is focused on the global understanding of the diesel soot oxidation on sintered metal filters (SMF). Platinum is studied as reference catalyst. The first objective is to determine which of platinum quantity, platinum particle size, or platinum location exhibits the preponderant influence on the catalytic.